Irrigation Systems - Their Role in Water Requirements and the Performance of Grapevines - van Zyl, J .L.; van Huyssteen, L. (South African Journal of Enology and Viticulture, 2017)
Irrigation systems were evaluated in three major viticultural areas in South Africa as regards grapevine performance, must and wine quality and the saving of irrigation water. Furrow irrigation saved more than 50% on irrigation water compared to full surface flooding without affecting grape yield, pruning mass and must composition. The irrigation frequency, however, had to be adapted to the volume of soil wetted. Tricklers gave results comparable to that of furrows. In another viticultural region, tricklers saved 25-30% water and the vines yielded a more favourable sugar/acid ratio compared to micro-jets, sprinklers and flood irrigation. In a third trial on a compact silty soil, tricklers gave results similar to that of flooding. Grape yield was not affected by the irrigation system in any one of the trials. Crop factors to be used for irrigation planning and scheduling are presented.